The Improving Model of the Quality of Financial Statements and Successful Implementation of Local Financial Information Systems - Irfan Irfan; Eka Nurmala Sari; Muhyarsyah Muhyarsyah; Siti Irafah (International Journal of Business Economics (IJBE), 2020)
This study aims to (1) examine and analyze the influence of Human Resource (SDM) competence and the role of internal audit on the successful implementation of the Local Financial Information System (SKID) partially and simultaneously, (2) examine and analyze the competence of SDM and the role of internal audit on the quality of financial report partially and simultaneously,(3) examine and analyze the influence of SDM competence and the role of internal audit on the quality of financial reports on the successful implementation of the SKID. The object of this study is all provincials and district / city governments throughout North Sumatera. The sample of this study was 34 (thirty four). The data was collected by questionnaire, documentation, and interview methods. The analysis method used was path analysis using SPSS Program. The results of this study indicate that (1) SDM competence and the role of internal audit have no partial effect on the successful implementation of SKID (2) SDM competence, the role of internal audit doesn’t simultaneously affect the successful implementation of SKID (3) SDM competence and the role of internal audit have a significant effect partially to the quality of financial reports (4) the successful implementation of SKID  has no effect on the quality of financial reports (5) SDM competence, the role of internal audit, the successful implementation of SKID simultaneously affects the quality of financial reports (6) SDM competence and the role of internal audit have no effect on quality financial reports through the successful implementation of the local financial information system.